Phenotypic plasticity of Aloysia citrodora: anatomical changes to water availability and seasons - Thiesen, Leonardo Antonio; Pinheiro, Marcos Vinícius Marques; Holz, Evandro; Werner, Anderson; Eloy, Elder; Caron, Braulio Otomar; Schmidt, Denise (Comunicata Scientiae, 2022)
The objective was to evaluate the anatomical changes of the leaves of Aloysia citrodora submitted to different water availability during the seasons. The experiment was conducted in a greenhouse, in a randomized block design, bifactorial 4x4, with four seasonal factors (autumn, winter, spring, and summer) and simulations of water availability (25, 50, 75 and 100% of field capacity) with four repetitions. They were evaluated in μm: the thickness of the adaxial and abaxial cuticles, adaxial and abaxial epidermis, palisade and lacunous parenchyma, mesophyll and leaf thickness of the transversal section and the mesophyll and thickness of the main rib and the length and width of the vascular system. In the autumn season, there was a reduction in the width of the vascular system and the thickness of the adaxial cuticle under greater water availability. In winter and under low water availability, there was a reduction in the thickness of the cuticle and adaxial epidermis, lacunous parenchyma, mesophyll and leaf thickness, mesophyll and main rib thickness. In the spring with greater water availability increased in the adaxial and abaxial epidermis, mesophyll and thickness of the main rib, and length of the vascular system; and low water availability provided the greater thickness of the adaxial cuticle, palisade parenchyma, and leaf thickness. In the summer season with the greatest water availability, there was an increase in leaf thickness and adaxial cuticle and a reduction in palisade parenchyma, while low water availability increased the thickness of leaf mesophyll.